Effects of an Intervention Approach Based on the Meanings of Vocal Behaviours in Older People Living with a Major Neurocognitive Disorder: A Pilot Study - Bourbonnais, Anne; Ducharme, Francine; Landreville, Philippe; Michaud, Cécile; Gauthier, Marie-Andrée; Lavallée, Marie-Hélène (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2019)
Introduction: Vocal behaviours (VB) are frequent in long-term care facilities (LTCF) and have many negative consequences. Interventions to decrease VB have limited clinical impact. Objective: This pilot study aimed to provide preliminary evidence on the effects of an intervention approach based on the meanings of VB in older people living with a neurocognitive disorder in LTCF. Methods: A mixed methods action research study was used. Fourteen triads (n=43) made up of an older person who manifested VB, a family member, and formal caregivers were included. An approach based on the meanings of VB was implemented in five LTCF. Semi-structured interviews took place with some participants. Tools were used at four-time points to measure five variables: the frequency of VB, the well-being of older people, the perceived disruptiveness of VB, the partnership-based decision-making and the empowerment felt by family and formal caregivers. Results: The approach improved the perception of family and formal caregivers toward older people. This led to habit changes that influenced positively the frequency of VB and the well-being of older people. Formal and family caregivers also perceived VB as less disturbing and felt more empowered relatively to VB. The attitude of formal caregivers toward families evolved positively. No other changes were noted on partnership-based decision-making. Discussion and conclusion: This study indicates the potential of this approach to improve the well-being of older people who manifested VB, their families, and formal caregivers. This approach could be implemented in LTCF, tested and adapted for other behaviours.